2018
DOI: 10.3892/ol.2018.9482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FOXM1 inhibition and ionizing radiation on melanoma cells

Abstract: Metastatic melanoma can be highly refractory to conventional radiotherapy and chemotherapy but combinatorial-targeted therapeutics are showing greater promise on improving treatment efficacy. Previous studies have shown that knockdown of Forkhead box M1 (FOXM1) can sensitize various tumor types to radiation-induced cell death. The effect of combining radiation with a small molecule FOXM1 inhibitor, Siomycin A, on growth, death and migration of a metastatic melanoma cell line (SK-MEL-28) that overexpresses this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…After comprehensively considering the AUC values of the models constructed by diverse algorithms, in this study, the LASSO regression analysis and stepwise multivariate Cox regression analysis were applied to establish the CIAI signature. The study by SIU et al found that radiation combined with FOXM1 inhibition was a potent inducer of cell death and suppressor of migration in metastatic melanoma cells ( Lee et al, 2018 ). A previous study by Bergamasch et al has shown that TP63 inhibits p53-induced apoptosis in melanoma cells following the application of genotoxic drugs, which may serve as a strategy to overcome resistance ( Patel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…After comprehensively considering the AUC values of the models constructed by diverse algorithms, in this study, the LASSO regression analysis and stepwise multivariate Cox regression analysis were applied to establish the CIAI signature. The study by SIU et al found that radiation combined with FOXM1 inhibition was a potent inducer of cell death and suppressor of migration in metastatic melanoma cells ( Lee et al, 2018 ). A previous study by Bergamasch et al has shown that TP63 inhibits p53-induced apoptosis in melanoma cells following the application of genotoxic drugs, which may serve as a strategy to overcome resistance ( Patel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Siomycin A is a thiazole-based antibiotic, isolated from an endophytic Actinomycin sp, derived from the medicinal plant Acanthopanax senticosus (32), which is effective against several malignancies, such as pancreatic cancer, glioblastoma and melanoma (32)(33)(34)(35). The anticancer role of Siomycin A against various cancer cells is well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Forkhead box protein M1 (FOXM1) was known as a predictive factor for tumor progression, and its expression was relevant to a bad prognosis in numerous cancers, such as prostate carcinoma [5], breast carcinoma [6], hepatic carcinoma [7], renal carcinomas [8], and melanoma [9]. However, the correlation between the FOXM1 expression pattern in different human MIBC tissues and its role in carcinoma development was still unclear.…”
Section: Foxm1 and β-Catenin Are Potential Prognostic Markers In Muscmentioning
confidence: 99%